PRELIMINARY STUDY ON THE ORGANOLEPTIC QUALITY OF CORN-COWPEA COOKIES MADE FROM COMPOSITE CORN AND COWPEA FLOUR AS AN ANTIDIABETIC ALTERNATIVE FOODS - Hermalina Sinay; Ritha Lusian Karuwal (Science Map Journal, 2023)
Corn and cowpea from Kisar Island have been reported to have nutritional content. With its nutritional content, it will be very useful if it is combined into a cookies product that can be developed especially for diabetics. In order to be used in the manufacture of cookies, it is necessary to know the correct formulation between corn flour and cowpea flour, especially in local varieties from South West Maluku District, and also to know the organoleptic value of corn-cowpea cookies products. Thus, the purpose of this study was to test the organoleptic results of Corn-cowpea cookies with corn flour and cowpea flour as the basic ingredients. This study consisted of three combination treatments of corn flour and cowpea, namely P1 (50: 50), P2 (80: 20), and P3 (90: 10) with 3 replications. Assessment of organoleptic quality was carried out to 25 panelists which included crispness, texture, taste, color and smell. The data obtained were analyzed descriptively in the form of hedonic percentages of panelists on products with categories of strongly dislike, dislike, somewhat like, like, and really like. The results showed that on the crispness variable as much as 12% of the panelists really liked the P2 treatment (80: 20). On the texture variable, 20% of the panelists really liked the P2 treatment. For the taste variable, 8% of the panelists really liked the P3 treatment. On the color variable, 16% of the panelists really liked the P3 treatment, and for the smell variable, 12% of the panelists really liked P3. Based on these results, it can be concluded that for the variable of crispness and texture, the panelists liked the P2 treatment the most, while for the taste, color, and smell variables, the panelists liked P3 the most. Thus, the most acceptable treatment by the panelists was the combination treatment of corn and cowpea flour 80: 20 and 90: 10 (P2 and P3).